Herpes associated erythema multiforme - Kamala, K. A. (Medknow Publications & Media Pvt Ltd, 2011)
Erythema multiforme is an acute and a self-limiting mucocutaneous hypersensitivity reaction triggered by certain infections and medications. One of the most common predisposing factors for erythema multiforme is infection with herpes simplex virus. Herpes associated erythema multiforme (HAEM) is an acute exudative dermatic and mucosal disease caused by the infecting herpes simplex virus. It has recurrence and idiorestriction, characterized by increasing of CD4+T leukomonocyte. This article reports a case of HAEM in a 9-year-old girl, with a review of relevant literature, and discusses the pathophysiology and treatment of erythema multiforme triggered by herpes simplex virus